Kesiapan Operasional Bandar Udara Adi Soemarmo Boyolali pada Periode Natal dan Tahun Baru 2026 - Khotimah, Apriani Kusnul; Wahyudono, Wahyudono; Adriansyah, Feri (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
The modern aviation industry is the backbone of global mobility, yet it faces significant challenges from passenger surges, particularly during peak periods such as Christmas and New Year. This study aims to analyze the operational readiness of Adi Soemarmo Airport in Boyolali for the 2025 Christmas and 2026 New Year period. The research focuses on identifying strategies and implementing readiness in the areas of Human Resources (HR), Standard Operating Procedures (SOPs), and Infrastructure and Facilities, based on projected passenger growth and aircraft movements. This study uses a qualitative approach, collecting data through in-depth interviews with the Airport Operations Control Head (AOCH) and Apron Movement Control (AMC) Supervisor, direct field observations, and documenting Adi Soemarmo Airport's operational plans. The research results show that Adi Soemarmo Airport has made various proactive preparations for the 2025/2026 Christmas and New Year holidays. In terms of human resources, readiness is demonstrated by the optimization of shift schedules, the addition of BKO personnel, and refresher training. In terms of standard operating procedures (SOPs), the airport has procedures for handling passenger surges and emergency situations, which are continuously evaluated and disseminated. Meanwhile, infrastructure and facility readiness includes optimizing the use of check-in counters, expanding waiting rooms, and managing passenger flow. However, challenges such as passenger discipline in adhering to check-in times and the effectiveness of optimizing facility capacity during peak traffic still require further attention. This study concludes that Adi Soemarmo Airport has a strong foundation for preparedness, but continued improvement in implementation details and cross-sector coordination is crucial.